Pengaruh Kebijakan Instruksi Presiden No 1 Tahun 2025 terhadap Kepercayaan Publik: Studi pada Mahasiswa Universitas Jambi - Nurhayati Boang Manalu; Sutri Destemi Elsi; Aditya Romadhon (Lembaga Pengembangan Kinerja Dosen, 2025)
Presidential Instruction Number 1 of 2025 concerning State Expenditure Efficiency gave rise to a fiscal paradox at the beginning of the new administration, with a cut of Rp306.69 trillion facing a 17.9% APBN deficit for flagship programs such as Free Nutritious Meals, which triggered doubts about public trust, especially students at the University of Jambi affected by the BOPTN adjustment. This study analyzes the influence of student perceptions on the dimensions of effective-efficient (X1) and transparent-accountable (X2) policies on public trust (Y) as an indicator of government legitimacy. A quantitative survey approach was applied to 400 active students at the University of Jambi (proportional random sampling using the Slovin e=0.05 formula), with SPSS multiple linear regression analysis after classical assumption testing, validity (r> r-table), and reliability (Alpha Cronbach's 0.920 (x1); 0.949 (x2); 0.918 (y)). The results show a significant simultaneous effect (F=200.951; sig=0.000), partial X1 is dominant (t=7.116; β=0.162; sig=0.000) and X2 is significant (t=5.532; β=0.110; sig=0.000), with R²=0.503 explaining 50.3% of the variation in trust. The findings confirm the theory of Easton (1965) and Weber (1947) that efficiency performance evaluation shapes trust, so it is recommended that a real-time APBN dashboard, transparent communication to regional PTNs, and fiscal literacy strengthen the legitimacy of good governance.